An investigation on the effectiveness of cost control techniques on operational performance: a case study of Interfresh Ltd (Mazoe Citrus Estate) - Nkomo, Thandeka (Midlands State University, 2014)
The researcher aimed at investigating on the effectiveness of cost control techniques on operational performance at Interfresh ltd (Mazoe Citrus Estate). The company has been associated with high repair and maintenance costs, wastage and spoilage cost, labor cost without a proportional increase in revenue and negative significant variance which arose time and again within department thereby decreasing operational performance. This pointed out that cost control techniques employed by Interfresh ltd which includes budgeting ,Activity based costing ,Balance score card and Standard costing were not effective as these techniques are meant to maintain cost by considering effectively the use of facilities ,materials and employees within the organization. The study was carried out for the period of 2011 to 2013. The researcher mainly assessed literature by Scarlet 2006 who provided guidelines on cost control techniques and performance evaluation. Descriptive research design was used to fully satisfy the objective of the study because it gave room for the researcher to obtain important and useful data which was valid and reliable. Secondary and primary data were both used to obtain data. Secondary data such as audit reports and annual final report were used. Primary data collected data making use of questioners and interview questions to obtain data. The researcher found out that Interfresh ltd was employing cost controls ineffectively as negative variance continuously occurred and costs such as repair and maintenance ,wastage and spoilage increased resulting in a decrease in its operational performance. The cost control techniques were found not to be motivational to employees since only the top management and some middle management are involved. The study recommended that there should be workers involvement, benchmarking against competitors, make use of lean six sigma, training to be provided for employees, incentive programs to be implemented, control reports to be enhanced as they inform management on the activities taking place in the entity and implement just in time so as to improve on operational performance and effective cost control techniques.